SEQUENCE DIVERSITY OF BoLA-DRB3 GENE IN PAKISTANI DROMEDARY CAMEL - T. Hussain; M. E. Babar; M. Tariq Pervez (Journal of Animal and Plant Sciences, 2016)
BoLA-DRB3 gene is responsible for the differences in the susceptibility to infectious disease in mammals and is considered more-appropriate for comparative evolutionary studies. Here we present 247 bp sequence of BoLA-DRB3 gene exon 2 in 20 individuals of Mareecha camel breed and non-descript camels of Pakistan. We identified this gene highly polymorphic as 10 different polymorphic sites (3 singleton and 7 Parsimony informative sites) were detected that may be related to the variability in the immune responsiveness of different individuals to particular pathogens. Ten identified haplotypes showed haplotype diversity 0.879 and nucleotide diversity 0.01445. The phylogenetic tree was also constructed using MEGA ver. 5.05 which indicated close relationship between camel and Ovis aries. This is the preliminary report on MHC genes in Pakistani camel that may be useful for the association of polymorphisms with the disease resistance and tolerance to various infectious agents in different breeds of camel in future.
Keywords: BolA-DRB3 exon 2; Sequences; High polymorphism; Pakistani camel